Pengaruh Variasi Latihan Drill Smash Terhadap Keterampilan Smash Atlet Voli Klub Bina Putri Medan Tahun 2023 - Purba, Andi Nata; Barus, Jan Bobby Nesra; Nurkhoiroh , Nurkhoiroh (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the influence of drill smash training on the smash skills of Medan Women's Development Club athletes in 2023, where there are five variations of training, where the five training variations given are designed to improve smash skills in volleyball athletes of the Medan Women's Development Club. This research was conducted at the Bina Putri Medan club which is located at Jl. Mangaan No.1, Mabar, Medan Deli, North Sumatra. The sample of this study is 10 people who were selected using random sampling techniques. This research method is an experiment, by conducting an initial test (pretest), then the sample is given treatment in the form of a drill smash variation training program. With the training program prepared, then after approximately 6 weeks of undergoing the training program, the sample did a final test (posttest). The initial and final tests were taken using the smash test instrument. The data analysis technique uses the t-test in the hypothesis testing process. Based on the results of data analysis, it is known that there is an influence of drill smash training on the smash skills of Bina Putri Medan club athletes in 2023